NEW STEREOTYPES ABOUT MARRIAGE MIGRANTS IN SOUTH KOREA (CONTENT ANALYSIS OF MEDIA FOR EXAMPLE, “THE KOREA TIMES”) (Journal of Oriental Studies, 2019)
This article presents the results of a content analysis of the South Korean English-language MEDIA on marriage migrants. Newspapers are one of the first media, they play a significant role in public life, news- paper articles provide information about the current situation, notify the public about current events. Through the analysis of newspapers, it was found that the media displayed social reality does not always reflect the public consciousness. To examine the articles of the South Korean MEDIA were selected news- paper articles, one of the largest Korean newspaper publishing house “The Korea Times”. This newspaper is one of the largest and leading newspapers in South Korea, which are published in English. The authors believe that it is possible to have a chance to assert that Korean society concerns itself with the distrust of inter-ethnic marriages, removing from the whole Korean society, framing them within certain limits,   for which inter-ethnic marriages challenging exit.Key words: inter-ethnic marriages, families, multiculturalism, foreign, media.